The Influence Of Fear Of Missing Out (Fomo) And Celebrity Endorser Syifa Hadju On Impulse Buying With Hedonic Shopping Motivation As A Moderating Variable: (Study on Generation Z Consumers of Glad2Glow Products in Bandar Lampung City) - Putri Chantika Khairunnisa; Satria Bangsawan; ⁠Mutiasari Nur Wulan (Cita konsultindo, 2026)
The development of e-commerce and social media has driven changes in consumer behavior, particularly among Generation Z, in purchasing skincare products. This phenomenon is characterized by an increase in impulse buying behavior influenced by psychological and digital marketing factors. This study aims to analyze the influence of Fear of Missing Out (FOMO) and celebrity endorser Syifa Hadju on impulse buying, with hedonic shopping motivation as a moderating variable, among Generation Z consumers of Glad2Glow products in Bandar Lampung City. This study uses a quantitative approach with a survey method. Data were collected through questionnaires distributed to Generation Z consumers who had purchased Glad2Glow products, with the sample size determined using purposive sampling. Data analysis was performed using Partial Least Square Structural Equation Modeling (PLS-SEM) through SmartPLS software. The results showed that Fear of Missing Out (FOMO) and celebrity endorsers had a positive and significant effect on impulse buying. In addition, hedonic shopping motivation was found to moderate the influence of Fear of Missing Out (FOMO) and celebrity endorsers on impulse buying.